Virtuousness profiles in school organizations in relations to psychological well-being levels in Ecuadorian adolescents - Unda Villafuerte, Fernando (2020)
The purpose of this study was to analyze the relationship between perceived virtues in positive school organizations and levels of well-being in adolecents; and, establish profiles of positive or virtuous school organizations considering, on the one hand, the gender and type of funding and, on the other, the levels of psychological well-being present in Ecuadorian adolescents. The research is justified by the need to generate spaces and strategies for socialization and learning that enhance the integral development of boys and girls and their lasting well-being in contexts influenced by instantaneous pleasure and high intensity. For the study, a sample of 550 students (51.7% men) was considered. The research applied two instruments validated to Ecuadorian contexts: the scale of perceived virtuousness in school organizations and the scale of psychological well-being in adolescents. As a result of the statistical analysis, a moderate correlation was observed between the study variables. Next, and in order to enhance the analysis, a cluster analysis of average k and an analysis of variance (ANOVA) of one factor were carried out to establish profiles of psychological well-being in adolescents according to the level of virtuosity perceived in school organizations. The aforementioned analysis gave rise to three levels of school organizations (virtuous, in transit to virtuousness and little virtuousness) that interacted in their order with three levels of psychological well-being (strengthened, under construction and vulnerable). Finally, in the section conclusions, specific strategies were formulated to generate virtuous organizations linked with better levels of well-being in students.